Depression and anxiety among people with hypertension on follow-up in Eastern Ethiopia: A multi-center cross-sectional study - Abdisa, Lemesa; Letta, Shiferaw; Nigussie, Kabtamu (Frontiers in Psychiatry, 2022)
Background People with hypertension have a high risk of developing mental disorders, such as depression and/or anxiety. However, there is a paucity of data regarding comorbid depression and anxiety symptoms among people with hypertension in study settings. Objective The study determined the prevalence and associated factors of depression, and anxiety symptoms among people with hypertension on follow-up at public hospitals, in Eastern Ethiopia. Materials and methods A cross-sectional study was carried out among 471 people with hypertension who were randomly chosen from four public hospitals in Harar town and the Dire Dawa Administration. The data were collected by interviewer-administered structured questionnaires. A validated nine-item Patient Health Questionnaire and Generalized Anxiety Disorder scales were used to assess depression and anxiety symptoms, respectively. A logistic regression model was used to identify the association among depression, anxiety, and their predictors. An adjusted odds ratio and a 95% confidence interval were used to report the association. The statistical significance was set at a p-value of < 0.05. Results Depression and anxiety symptoms were present in 27.2 and 32.7% of people with hypertension, respectively. Being women (AOR = 1.74, 1.09–2.78), having no formal education (AOR = 2.19, 1.19–4.81), presence of other medical illnesses (AOR = 2.23, 1.39–3.56), having a family history of depression (AOR = 2.01, 1.25–3.19), and poor social support (AOR = 2.80, 1.60–5.22) were statistically associated with depressive symptoms, whereas being women (AOR = 1.54, 1.01–2.35), widowed and divorced (AOR = 2.22, 1.41–3.52), presence of other medical illnesses (AOR = 1.64, 1.06–2.53), and poor social support (AOR = 3.54, 2.09–6.01) were statistically associated with anxiety symptoms. Conclusion More than a quarter of people with hypertension reported symptoms of depression and anxiety. Findings demonstrated that being a woman, having an additional medical illness and having poor social support were statistically associated with depressive and anxiety symptoms. Regular screening, early detection, and offering the proper intervention should be on top priorities for healthcare professionals.